2021
DOI: 10.1021/acs.jpcc.1c08362
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Random Lasers Based on Perovskite Quantum Dots Embedded in Intrinsic Pb–MOFs

Abstract: Perovskite quantum dots (PQDs) have attracted extensive attention for various applications due to their hallmark optoelectronic properties. However, PQD gain materials are usually needed to be integrated with an external cavity to acquire effective optical feedback for lasing oscillation, which generally suffers from stringent fabrication procedures and the destruction of their pristine gain performance. In this work, we propose an approach to realize a new class of random lasers that are constructed by in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…13 Compared to other MOFs with outstanding adsorption properties, white Pb-MOF powders exhibit great potential as a luminescent matrix. 33 The Pb-MOFs were added, and they acted as substrates to provide Pb 2+ sites for the in situ synthesis of CsPbBr 3 NCs and obtain high-density CsPbBr 3 @Pb-MOF composites. The irregular rectangular morphology shown in Figure 1b 220) planes of cubic CsPbBr 3 NCs, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Compared to other MOFs with outstanding adsorption properties, white Pb-MOF powders exhibit great potential as a luminescent matrix. 33 The Pb-MOFs were added, and they acted as substrates to provide Pb 2+ sites for the in situ synthesis of CsPbBr 3 NCs and obtain high-density CsPbBr 3 @Pb-MOF composites. The irregular rectangular morphology shown in Figure 1b 220) planes of cubic CsPbBr 3 NCs, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that Pb 2+ coordinated with a 1,3,5-H 3 BTC 2– molecule and two H 2 O molecules to form a two-dimensional polymer structure in aqueous solution . Compared to other MOFs with outstanding adsorption properties, white Pb-MOF powders exhibit great potential as a luminescent matrix . The Pb-MOFs were added, and they acted as substrates to provide Pb 2+ sites for the in situ synthesis of CsPbBr 3 NCs and obtain high-density CsPbBr 3 @Pb-MOF composites.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the reversible luminescence intensity changes and spectral shifts of CdSe QD clusters have illustrated the potential for developing sensors based on quantum dot nanoscale components. However, there are still certain flaws accompanying the application of quantum dots, such as weak temperature resistance, which leads to reduced optical performances of quantum dot sensors and rapid annihilation at higher temperatures. , Besides, the limited accuracy of quantum dot sensors and the requirement to adjust their laser intensity and distance during monitoring processes further restrict their application as sensors. Therefore, achieving high ubiquity, high accuracy, and noncontact temperature detection in the existing technology for detecting the workings condition of mechanical components remains a dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…11 Secondly, MOFs usually have a high refractive index, and thus, provide vital feedback to photons. 12,13 MOFs can also easily form high-quality micro/nano-sized crystals that can be used as natural micro/nano optical cavities. By combining these above advantages, some micro/nanolasers based on MOFs have been reported successively in recent years.…”
Section: Introductionmentioning
confidence: 99%